LITERASI MEDIA PADA GENERASI MILENIAL DI ERA DIGITAL - SAPTA SARI (UNIVED PRESS, Universitas Dehasen Bengkulu, 2019)
Media literacy in the Millennial generation in the digital era is still not well implemented. We still see and read a lot of information that is still not clear the truth on social media. This research was conducted to see how media literacy in the Millennial generation in the digital era, especially in social media. Research uses a qualitative method with a literature study approach, by analyzing theories and analyzing based on phenomena that occur so that a comprehensive understanding of the application of media literacy in Millennials in the digital age is obtained. The results of the study revealed, first the literacy of the pause in the digital age is still not well implemented in society even though they are already adept at using digital devices. This bias can be seen that there is still a lot of information found that the truth is not yet distributed in social media by Millennials. Second, the Millennial generation is the term for the generation born in the 1980 to 2000 range. Those who are said to be the Millennial generation are the generation who are currently aged 19 to 40 years, or school age to productive / worker age. Third, Millennial generation interaction with social media in the digital era is very intense. This generation is very ska surfing on social media to share information, entertainment, highlight their existence, mingle with the community in chat groups. Fourth, the development of media literacy in the Millennial generation in the digital era is still not as expected. Millennials do not have good knowledge about media literacy, so there are still many violations in social media, especially in terms of filtering and disseminating information to the public. Keywords: media literacy, millennial generation, media literacy in the digital era